Tractus Errores Graecorum: Polemics of the Latin Patriarchate of Constantinople against the Greeks - Jack Hanrahan-Shirley (Athens Journal of History)
This paper examines the Latin text entitled Tractus Errores Graecorum: De Processione Spiritus Sancti. De Animabus Defunctorum. De Azymis Et Fermentato, De Obedientia Romanae Ecclesiae, most probably written and published in 1252 in Constantinople, attributed to the deacon Pantaleone. Attention will be specifically given to the argumentation utilized by Pantaleone to attack the theological and liturgical positions advocated for and defended by his Byzantine opponents. This paper is the first examination of the text by modern English-language scholarship. The analysis of the Tractus Errores Graecorum put forward in this paper provides crucial insights into the history and development of Latin polemics against the Byzantines during the 13th century in the context of the Latin Empire of Constantinople.